Investigation of the Molecular Role of Brain-Derived Neurotrophic Factor in Alzheimer’s Disease - Girotra, Pragya; Behl, Tapan; Sehgal, Aayush; Singh, Sukhbir; Bungau, Simona (Journal of molecular neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF), or abrineurin, is a member of the neurotrophin family of growth factors that acts on both the central and peripheral nervous systems. BDNF is also well known for its cardinal role in normal neural maturation. It binds to at least two receptors at the cell surface known as tyrosine kinase B (TrkB) and p75 NTR . Additional neurotrophins that are anatomically linked with BDNF include neurotrophin-3 (NT-3), neurotrophin-4 (NT-4), and nerve growth factor (NGF). It is evident that BDNF levels in patients with Alzheimer’s disease (AD) are altered. AD is a progressive disorder and a form of dementia, where the mental function of an elderly person is disrupted. It is associated with a progressive decline in cognitive function, which mainly targets the thinking, memory, and behavior of the person. The degeneration of neurons occurs in the cerebral cortex region of brain. The two major sources responsible for neuronal degeneration are protein fragment amyloid-beta (Aβ), which builds up in the spaces between the nerve cells, known as plaques, disrupting the neuron signaling pathway and leading to dementia, and neurofibrillary tangles (NFTs), which are the twisted fibers of proteins that build up inside the cells. AD is highly prevalent, with recent data indicating nearly 5.8 million Americans aged 65 and older with AD in 2020, and with 80% of patients 75 and older. AD is recognized as the sixth leading cause of death in the USA, and its prevalence is predicted to increase exponentially in the coming years. As AD worsens over time, it becomes increasingly important to understand the exact pathophysiology, biomarkers, and treatment. In this article, we focus primarily on the controversial aspect of BDNF in AD, including its influence on various other proteins and enzymes and the current treatments associated with BDNF, along with future perspectives.